Efficacy of pembrolizumab for patients with both high PD‐L1 expression and an MET exon 14 skipping mutation: A case report. Issue 2 (2nd January 2019) - Baba, Keisuke; Tanaka, Hisashi; Sakamoto, Hiroaki; Shiratori, Toshihiro; Tsuchiya, Junichiro; Ishioka, Yoshiko; Itoga, Masamichi; Taima, Kageaki; Tasaka, Sadatomo
Abstract : Pembrolizumab has become the standard first‐line treatment for non‐small cell lung cancer (NSCLC) patients with high PD‐L1expression. MET exon 14 skipping is a rare mutation typically found in older, female, and non‐smoking patients with NSCLC. Herein, we report the case of a 71‐year‐old non‐smoking woman who was diagnosed with NSCLC in the left lung. EGFR mutation and ALK fusion were not detected. Because the biopsy specimen showed high PD‐L1 expression with a tumor proportion score of 95%, pembrolizumab was introduced as first‐line therapy, but resulted in no clinical benefit. The patient was subsequently administered chemotherapy with carboplatin and pemetrexed, leading to remarkable tumor shrinkage. A next‐generation sequencing panel analysis revealed a MET exon 14 skipping mutation. Thus, pembrolizumab might not be effective for NSCLC patients with MET exon 14 skipping mutations, even if PD‐L1 expression is high.